Nanotoxicity of engineered nanomaterials (ENMs) to environmentally relevant beneficial soil bacteria – a critical review. Issue 3 (16th March 2019) - Lewis, Ricky W.; Bertsch, Paul M.; McNear, David H.
Abstract: Deposition of engineered nanomaterials (ENMs) in various environmental compartments is projected to continue rising exponentially. Terrestrial environments are expected to be the largest repository for environmentally released ENMs. Because ENMs are enriched in biosolids during wastewater treatment, agriculturally applied biosolids facilitate ENM exposure of key soil micro-organisms, such as plant growth-promoting rhizobacteria (PGPR). The ecological ramifications of increasing levels of ENM exposure of terrestrial micro-organisms are not clearly understood, but a growing body of research has investigated the toxicity of ENMs to various soil bacteria using a myriad of toxicity end-points and experimental procedures. This review explores what is known regarding ENM toxicity to important soil bacteria, with a focus on ENMs which are expected to accumulate in terrestrial ecosystems at the highest concentrations and pose the greatest potential threat to soil micro-organisms having potential indirect detrimental effects on plant growth. Knowledge gaps in the fundamental understanding of nanotoxicity to bacteria are identified, including the role of physicochemical properties of ENMs in toxicity responses, particularly in agriculturally relevant micro-organisms. Strategies for improving the impact of future research through the implementation of in-depth ENM characterization and use of necessary experimental controls are proposed. The future of nanotoxicological research employing microbial ecoreceptors is also explored, highlighting the need for continued research utilizing bacterial isolates while concurrently expanding efforts to study ENM–bacteria interactions in more complex environmentally relevant media, e.g. soil. Additionally, the particular importance of future work to extensively examine nanotoxicity in the context of bacterial ecosystem function, especially of plant growth-promoting agents, is proposed.